Analysis of Factors Affecting Hypertension Control in the Elderly at the Meukek Health Center Uptd, Meukek District, South Aceh Regency - Salbiyah, Salbiyah; Asriwati , Asriwati; Efendy, Ismail; Fitria, Aida (PSPP JOURNALS, 2024)
Hypertension is one of the problems that often occurs in the elderly. Prevalence hypertension in Indonesia is experiencing decrease. However, hypertension is factor risk highest reason death fourth in Indonesia. In South Aceh, the prevalence hypertension also experienced improvement for 3 years Lastly. Likewise with the UPTD Puskesmas Meukek who experienced improvement case hypertension in the elderly. Some factors that influence control hypertension among them obesity, activity physical , and restrictions salt consumption. Study This aiming For analyze factors that influence control hypertension in the elderly at the UPTD Health Center Meukek Anxiety Meukek South Aceh Regency. This type of research is analytical with a cross-sectional design. The population in this study were all elderly people aged >60 years who had a history of hypertension with a sample of 66 people. The sampling technique used the cluster proportional sampling technique. Data were obtained by distributing questionnaires. The data analysis method was analyzed in a way univariate , bivariate with using the Chi-Square test, and multivariate using regression test logistics multiple with at the level 95% confidence. Research result show factors that influence control hypertension in the elderly that is obesity (p-value = 0.026), activity physical (p-value = 0.002), restrictions salt consumption (p-value = 0.010). The most dominant factor influence control hypertension in the elderly is activity physique with Exp(B) value = 15.905. Elderly with activity physique good 15 times effect to control hypertension in the elderly. It is expected to Respondent For control obesity through pattern eat a balanced and healthy diet, do activity physique light routine activities regular physical such as walking, and increase knowledge elderly For reduce salt consumption with do dissemination and socialization in activities post office.